Controllable in-situ-oxidization of 3D-networked Ti3C2Tx-TiO2 photodetectors for large-area flexible optical imaging. (March 2022) - Xiong, Da; Deng, Weili; Tian, Guo; Zhang, Binbin; Zhong, Shen; Xie, Yanting; Yang, Tao; Zhao, Haibo; Yang, Weiqing
Abstract: The intrinsic hydrophilicity of MXenes makes a promise for the large-area fabrication of flexible optoelectronic devices. However, the inferior optical absorption and high scattering rate of pure MXenes severely limit its practical application in photodetectors. Here, we demonstrate a controllable in - situ -oxidization strategy for the large-scale fabrication of 3D-networked Ti3 C2 T x -TiO2 heterostructure for photodetectors. Benefiting from the enhanced optical absorption and the enlarged carrier transport efficiency, this photodetector can achieve 13.3 times performance improvement than that of the pristine Ti3 C2 T x under 405 nm (8.58 mW) light illumination at 5 V bias. Furthermore, the as-developed 3D-networked Ti3 C2 T x -TiO2 photodetectors can be conveniently fabricated into a large-area array (10 × 10 cm 2 ), which can effectively image the shape of "p" letter as well as more complex circular patterns, indicating the huge potential of large-area flexible optical imaging. Evidently, this controllable in - situ -oxidization strategy paves a way for the construction of versatile 3D-networked functional materials for electronic devices. Graphical Abstract: This work demonstrates a controllable in - situ -oxidization strategy for the large-scale fabrication of 3D-networked Ti3 C2 T x -TiO2 heterostructure photodetectors array for optical imaging. The fabricated photodetectors achieve 13.3-fold performance improvement due to the optimized optical absorption and carrier transport. Evidently, this strategy can provide a feasible way to construct versatile 3D-networked functional materials for electronic devices. ga1 Highlights: A 3D-networked Ti3 C2 T x -TiO2 heterostructure was constructed via the proposed controllable in-situ -oxidization strategy. The 3D-networked heterostructure enhanced the performance of photodetectors due to the improved the optical absorption and excitons separation. The developed photodetectors can be conveniently fabricated into a large-area array for optical imaging.